Wireless communication system for unmanned vehicle - Fan, Yunqi (2014)
With the maturing of applicable technologies, Unmanned Aerial Vehicle (UAV) has been given a higher priority in recent society because of its great scientific significance and widespread application value especially in the information field. A means of communication for UAV available at present is to use Ultra-wide band impulse radio (UWB-IR) technology. This project involves hardware and software development of a wireless communication system for communication between an UAV and a control site in an indoor environment. The real-time data collected from sensors on UAV was sent to a microcontroller and repackaged before transmitted through UWB front-end. Another microcontroller collected data from the UWB receiver and decoded them on the receiving end. Finally, the acquired data was uploaded to a PC and visualized using Code Composer Studio (CCS) graph tool to demonstrate the performance.